2014
DOI: 10.1371/journal.pone.0113573
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Metabolic Alterations in Human Cells Exposed to Gamma Irradiation

Abstract: Radiation exposure is a threat to public health because it causes many diseases, such as cancers and birth defects, due to genetic modification of cells. Compared with the past, a greater number of people are more frequently exposed to higher levels of radioactivity today, not least due to the increased use of diagnostic and therapeutic radiation-emitting devices. In this study, ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS)-based metabolic profiling was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 41 publications
4
50
0
Order By: Relevance
“…Both cell types reacted with reduced proliferation upon irradiation. These results are in line with the findings of the proliferation assay and support both our and others′ previously published data of a diminished cell viability of fibroblasts …”
Section: Discussionsupporting
confidence: 93%
“…Both cell types reacted with reduced proliferation upon irradiation. These results are in line with the findings of the proliferation assay and support both our and others′ previously published data of a diminished cell viability of fibroblasts …”
Section: Discussionsupporting
confidence: 93%
“…Similarly, o ‐phosphocholine decreased by more than 64% in the spleen and o ‐phosphoethanolamine decreased by more than 35% in the high‐dose radiation group. One study demonstrated that changes in the levels of phospholipid‐metabolism‐associated metabolites indicate ROS‐induced membrane damage caused by radiation . Total choline levels also change significantly as a result of changes in membrane choline phospholipid metabolism in response to increasing amounts of radiation .…”
Section: Discussionmentioning
confidence: 99%
“…Histological and ultrastructure examination in the present study were observed after 72 h from radiation exposure to quit cell's adaptive protection against an array of exogenous attack (Kwon et al, 2014). Our major observed anomalies in the midgut epithelium of B. polycresta were in the nucleus of both the regenerative and the digestive cells.…”
Section: Discussionmentioning
confidence: 53%